Design, Synthesis, and Biological Activity of Oxime Ether Strobilurin Derivatives Containing Indole Moiety as Novel Fungicide. (15th November 2014) - Xie, Ya‐Qiang; Huang, Zi‐Long; Yan, Hui‐Dong; Li, Jun; Ye, Li‐Yi; Che, Li‐Ming; Tu, Song
<x xml:space="preserve">Abstract</x> Twenty‐one novel oxime ether strobilurins containing indole moiety, which employed an indole group to stabilize the E‐styryl group in Enoxastrobin, were designed and synthesized. The biological assay indicated that most compounds exhibited potent fungicidal activities. The structure–activity relationship study demonstrated that the synthesized methyl 3‐methoxypropenoate oxime ethers 7b–e exhibited remarkably high activities among all the synthesized oxime ether compounds 7. Moreover, the fungicidal activities of methyl α‐(methoxyimino)benzeneacetate oxime ethers compounds 7f–i and N‐methoxy‐carbamic acid methyl esters compounds 7j–m showed significant differences compared to the corresponding products of ammonolysis.